Value of lung biopsy in pulmonary diseases in children - Al-Nassar S; Kadamba P; Habib Z (Wolters Kluwer Medknow Publications, 2006)
Purpose: Open lung biopsy (OLB) is claimed to be a sensitive tool for the diagnosis of interstitial lung disease. It is reported to be associated with significant morbidity and mortality. Aim: Evaluate whether lung biopsy helped us to make a specific diagnosis, it had resulted in change in therapy and assessment of its morbidity and mortality. Materials and Methods: This was a retrospective analysis of 91 lung biopsies performed in 83 patients between January 2000 and December 2003. These children were allocated to three groups: a. Primary pulmonary pathology (22), b. Immunocompromised (49) i. Primary immunodeficiency (10), ii. Postchemotherapy and BMT (39), c. Pulmonary metastases from solid tumors (20) Results: A specific diagnosis was reached in 87/91 children (95%), but this resulted in a change in therapy (excluding lung meet) in only 23/71 (32%). It is lower in those postchemo/BMT 8/39 (20.6%). Postoperative morbidity occurred in 11/91 (12%) but procedure-related morbidity was only (3.2%). Death within a month of the biopsy occurred in six children (6.5%), with one (1.1%) procedure-related. Conclusion: 1. OLB is a safe procedure at our institution. 2. OLB is a sensitive tool to determine the specific cause of pulmonary infiltrate. 3. Change in therapy expected to be only in 32% of patients and even lower in postchemotherapy and BMT children.